- #1

chatterbug219

- 15

- 0

## Homework Statement

Solve the system of differential equations:

y'(t) + z(t) = t

y"(t) - z(t) = e

^{-t}

Subject to y(0) = 3, y'(0) = -2, and z(0) = 0

## Homework Equations

My professor did an example in class that was much simpler and solved it using Kramer's rule.

## The Attempt at a Solution

I don't know how to start it. I thought about rearranging the equations so that one was equal to y'(t) and the other was equal to z(t), but I'm not sure that would work...